The Effectiveness Of Electronic Signatures In Civil Contracts In The Digital Era - Nurmin K. Martam (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Digital transformation has brought significant changes in various aspects of life, including in the realm of law, especially civil contracts. Electronic signature is one of the important innovations that offer efficiency, flexibility, and convenience in contract transactions in the digital era. This research aims to examine the effectiveness of the use of electronic signatures in civil contracts, especially in terms of legal validity, security, and acceptance by the public and business actors. The results show that electronic signatures in Indonesia have been legally recognized based on Law Number 19 of 2016 amending Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law). However, while e-signatures have great potential to speed up the contracting process, several challenges remain, such as security concerns and resistance among small and medium-sized enterprises (SMEs). Security issues are a major concern, given the risk of cybercrime such as hacking and digital identity forgery. In addition, low digital literacy in the society hinders the widespread adoption of e-signatures.